Cultural Diplomacy in Cold War Finland Identity, Geopolitics and the Welfare State - Clerc, Louis (Palgrave Macmillan Series in Global Public Diplomacy,, 2023)
This open access book explores the organization and evolution of Finland's Cold War cultural diplomacy (1945-1975) as the basis for a reflection on the country's foreign relations, the link between culture and politics, small states' autonomy during the Cold War, and the porosity of the East-West divide. The book offers a historical survey of the development of Finland's cultural diplomacy as part of the Finnish state's foreign activities. In its empirical parts, it focuses on archives drawn from the Finnish Ministry of Foreign Affairs and the Ministry of Education in order to explain Finland's cultural diplomacy as the result of the country's foreign policy orientations, interactions between domestic and foreign policy, and the expansion of state activities in the artistic, educational, and cultural sectors. Various reflections and reports on foreign cultural relations highlight the role of identity concerns, cultural relations, geopolitics and economic imperativesin the development of a specifically Finnish cultural diplomacy. Furthermore, the book focuses on specific aspects and events, considering for instance the organization and evolutions of Finland's cultural relations with the USSR, the role of cultural treaties, academic exchanges and scientific cooperation, "cultural exports" and the marketization of culture, overlaps between cultural relations and high politics. Louis Clerc is Professor in Contemporary History in the Department of Contemporary History, Philosophy and Political Science at the University of Turku, Finland. His current research projects deal with the history of public and cultural diplomacy and the study of diplomatic relations.